NAFKAH MADIYAH ANAK DALAM PERSPEKTIF MASLAHAT MURSALAH NAJMUDDIN AT-THUFI: MADIYAH CHILDREN'S FEEDBACK IN THE PERSPECTIVE OF MASLAHAT MURSALAH NAJMUDDIN AT-THUFI - Abda, Muhammad Syafqy; Habibah, Nor; Mursyada, Ahmad (Mitsaqan Ghalizan, 2022)
Nafkah Madhiyah for children in Religious Court's lawsuits now has different legal provisions. It were initially declared inviolable then now became opened for accusations thence provides opportunities for children to get these rights. The child's livelihood is the responsibility of a father, as contained in the Qur'an and regulated in the Marriage Law. There are several opinions of scholars that abolish the child's middle income, as well as the Supreme Court Jurisprudence Number 608/K/AG/2003 which states that basically Madhiyah's income cannot be sued because the child's income is Lil' Intifa, namely to take benefits, not Lit Tamlik or to be owned. Then the negligence of a father who does not provide a sustenance for his child or Nafkah Madhiyah maintenance cannot be sued, but with the legal breakthrough contained in SEMA No. 2 of 2019 which states that the child's Nafkah Madhiyah can be asked. This paper attempts to see the relevance of the SEMA with the maslahah mursalah put forward by Najmuddin at-Thufi.